Изображения на Паисий Хилендарски върху българските пощенски марки. „Царският Паисий“ - Кръстева, Мила (Slavica Lodziensia, 2019)
The author analyzes the images of Paisii Hilendarski, printed on Bulgarian postage stamps. It is shown that in Bulgaria for a period of 92 years (1920–2012) a total of 10 postage stamps have been validated. They reflect the memory of the Bulgarians: both for Paisii and for Slavo-Bulgarian History. It is suggested that every Bulgarian cultural and historical age imposes its own rules on how to display the monk from Hilendar. The article follows the program of the project: ‘From one man’s lips to another’s ear’ … and all the way to the Internet’ (Project № FP-17 FlF-004/16.05.2017, Department for Scientific Research, Plovdiv University ‘Paisii Hilendarski’).